Evaluation and management of abdominal stab wounds: A Western Trauma Association critical decisions algorithm. Issue 5 (November 2018) - Martin, Matthew J.; Brown, Carlos V.R.; Shatz, David V.; Alam, Hasan B.; Brasel, Karen J.; Hauser, Carl J.; de Moya, Marc; Moore, Ernest E.; Rowell, Susan E.; Vercruysse, Gary A.; Baron, Bonny J.; Inaba, Kenji
Abstract : ABSTRACT: This is a recommended management algorithm from the Western Trauma Association addressing the management of adult patients with abdominal stab wounds. Because there is a paucity of published prospective randomized clinical trials that have generated Class I data, these recommendations are based primarily on published observational studies and expert opinion of Western Trauma Association members. The algorithm and accompanying comments represent a safe and sensible approach that can be followed at most trauma centers. We recognize that there will be patient, personnel, institutional, and situational factors that may warrant or require deviation from the recommended algorithm. We encourage institutions to use this as a guideline to develop their own local protocols.